Critique of Intellectual Property Law Supervision and Policy: Towards a Structured System in Indonesia - Nurwati Nurwati; Radif Khotamir Rusli; Martin Roestamy; Adi Rahman Nur Ibnu (Universitas Muhammadiyah Purwokerto, 2025)
Intellectual property (IP) law plays a crucial role in fostering innovation, creativity, and economic growth by safeguarding intellectual assets such as inventions, trademarks, and artistic works. However, the rapidly evolving technological landscape, globalization, and the rise of digital platforms have exposed significant shortcomings in existing IP legal frameworks. Key challenges include inconsistent enforcement mechanisms, fragmented legal systems, online piracy, and insufficient stakeholder awareness, particularly in developing economies. Despite attempts at reform, IP policies often remain reactive and disconnected, limiting their ability to address cross-border complexities and technological advancements effectively. This study critically evaluates the current state of IP law, identifying gaps and proposing solutions for a cohesive, proactive framework. Employing a normative legal approach, it examines statutory provisions, case law, and policy documents, with key references including the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), WIPO standards, and regional agreements. Comparative analyses of the US, EU, and Japan provide insights into best practices and highlight policy deficiencies. The findings underscore five critical issues: weak enforcement mechanisms, fragmented legal frameworks, digital challenges, low stakeholder awareness, and gaps in international cooperation. The study advocates for harmonized enforcement strategies, increased stakeholder education, and strengthened cross-border collaboration. These recommendations aim to establish an adaptive IP system aligned with technological progress, fostering global innovation and effectively protecting creators and businesses.